2022
DOI: 10.1038/s41388-022-02457-w
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived exosomes deliver the tumor suppressor miR-3591-3p to induce M2 macrophage polarization and promote glioma progression

Abstract: Exosomes can selectively secrete harmful metabolic substances from cells to maintain cellular homeostasis, and complex crosstalk occurs between exosomes and tumor-associated macrophages (TAMs) in the glioma immune microenvironment. However, the precise mechanisms by which these exosome-encapsulated cargos create an immunosuppressive microenvironment remain unclear. Herein, we investigated the effect of glioma-derived exosomes (GDEs) on macrophage polarization and glioma progression. We performed sequencing ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…Zeng et al also found that activation of the JAK2/ STAT3 signaling pathway promoted the polarization of M2 macrophages, which in turn decreased the levels of inflammatory factors IL-1b, TNF-a and IL-18 while increasing the levels of antiinflammatory factor IL-10 significantly improved the skin lesions in mice with atopic dermatitis (44). Other studies, especially those related to tumor diseases such as ovarian cancer and glioma, have shown that activation of the JAK/STAT3 signaling axis facilitates M2 macrophage polarization and affects disease progression by activating or inhibiting related cytokines (45)(46)(47)(48)(49). The two completely opposite types of results imply that macrophage polarization is not only related to the heterogeneity of STAT3 and macrophages themselves, but also influenced by the JAK/ STAT3 pathway, as well as multiple cytokines, chemokines, immune cells, tumor cells, and crosstalk of different signaling pathways in macrophages (50, 51).…”
Section: Stat3 Regulates Macrophage Polarization Through the Jak/stat...mentioning
confidence: 99%
“…Zeng et al also found that activation of the JAK2/ STAT3 signaling pathway promoted the polarization of M2 macrophages, which in turn decreased the levels of inflammatory factors IL-1b, TNF-a and IL-18 while increasing the levels of antiinflammatory factor IL-10 significantly improved the skin lesions in mice with atopic dermatitis (44). Other studies, especially those related to tumor diseases such as ovarian cancer and glioma, have shown that activation of the JAK/STAT3 signaling axis facilitates M2 macrophage polarization and affects disease progression by activating or inhibiting related cytokines (45)(46)(47)(48)(49). The two completely opposite types of results imply that macrophage polarization is not only related to the heterogeneity of STAT3 and macrophages themselves, but also influenced by the JAK/ STAT3 pathway, as well as multiple cytokines, chemokines, immune cells, tumor cells, and crosstalk of different signaling pathways in macrophages (50, 51).…”
Section: Stat3 Regulates Macrophage Polarization Through the Jak/stat...mentioning
confidence: 99%
“…Studies show that TAMs tend to polarize to the M2 phenotype by activating the JAK2/STAT3 pathway. For instance, IL‐8, MAPK, IL‐6, IRF3, IL‐10 and even cigarette extracts can promote M2 polarization in TAMs by activating the JAK2/STAT3 pathway 49–53 . On the other hand, ceramide and palmitic acid are known to inhibit M2 polarization by downregulating IL‐10 88 .…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma tissue is surrounded by massive immune cell infiltration, resulting in the creation of a complex immune microenvironment that allows osteosarcoma cells to grow within the bone by creating an immunosuppressive microenvironment to maintain their survival and proliferation. [35][36][37] A robust immunosuppressive microenvironment is positively correlated with overactivation of molecules associated with immune suppression, such as indoleamine 2,3-dioxygenase (IDO), programmed cell death protein 1 (PD-1), interleukin-10 (IL-10), transforming growth factor-β (TGF-β), vascular endothelial growth factor (VEGF), and signal transducer and activator of transcription 3 (STAT3), due to their immunosuppressive effects mediated by myeloid-derived suppressor cells (MDSCs), TAMs, and regulatory T lymphocytes (Tregs) [38][39][40][41][42][43] (Fig. 2).…”
Section: The Immune Microenvironment Of Osteosarcomamentioning
confidence: 99%